Antiviral Activity of Nobiletin against Chikungunya virus in vitro. Issue 8 (November 2017) - Lin, Shih-Chao; Chen, Mei-Chun; Li, Shiming; Lin, Chi-Chen; Wang, Tony T
Background: Chikungunya virus (CHIKV), a highly contagious re-emerging virus, is transmitted by infected mosquitoes. CHIKV is prevalent in tropical countries and is continuing to creep farther north into temperate areas. CHIKV is responsible for induction of chikungunya fever (CF) and severe joint stiffness with the capability of developing into bilateral and systemic arthralgia or even encephalitis. Despite the high morbidity rate, no approved antiviral drug is available. Therefore, an anti-CHIKV therapy is necessary to control this disease. In this study, we screened four flavonoids for anti-CHIKV activities: nobiletin, phlorizin, resveratrol and oxyresveratrol. Methods: We performed MTT, Viral ToxGlo TM and lactate dehydrogenase (LDH) assays to assess the viability of CHIKV-infected host cells. Plaque assay and immunofluorescent assay were utilized to evaluate the levels of viral production in quantification and qualification, respectively. Results: We first confirmed that nobiletin can maintain the cellular survival of infected cells without inducing significant toxicity to host cells. Nobiletin suppressed virus-induced cell death and viral production. Also, the antiviral efficacy of nobiletin can last for at least 48 h during infection. More importantly, nobiletin inhibited CHIKV infection during the translation/replication stages and viral entry, making nobiletin a potential clinical antiviral agent in prophylaxis and post-exposure treatment. Conclusions: In this study, our results provided a strategy to develop anti-chikungunya agents by utilizing natural compounds. Also, we believe that nobiletin can be a potential antiviral agent against CHIKV infection worthy of being further investigated as a remedial candidate in vivo .